PENGARUH VARIASI SUDUT WINGLET DAN SUDUT PITCH TERHADAP CUT IN SPEED PADA TURBIN ANGIN POROS HORIZONTAL - Dzakwan Murtadlo Mukti Mukti; Danar Susilo Wijayanto; Taufik Wisnu Saputra (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
Horizontal axis wind turbine is to convert mechanical energy in the wind and next change to electrical energy from generator. In this study done using Horizontal axis wind turbine type NACA 4412 for determine winglet angle variation on the end of blade and used, with winglet angle variation 150, 300, 450, 600 with the addition of pitch angle 100, 120, 140, 160, 180 and five blade. The purpose of this study is to find out how much influence the variation in winglet angle and pitch angle on the cut in speed produced by horizontal wind turbines. The method used in this study is to use the experimental method. samples used in this study using the NACA 4412 Horizontal wind turbine.The best cut in speed obtained in this study was obtained by the variation in winglet angle 15, where the cut in speed values obtained against the variation in pitch angle were 100 (0.91 m/s), 120 (0.77 m/s), 140 (0.77 m/s), 160 (0.71 m/s), and 180 (0.73 m/s) and and pitch angle variation 18, where the cut in speed values obtained against winglet angle variations are 600 (0.82 m/s), 450 (0.84 m/s), 300 (0.8 m/s), and 150 (0.73 m/s).